Peculiarities of Turkey’s Integration into the Chinese Initiative “One Belt - One Way” - G. N. Valiakhmetova; M. A. German (Научный диалог, 2020)
The evolution of bilateral relations between the PRC and the Republic of Turkey is examined in the context of the integration of the Turkish project “Central Corridor” into the Chinese initiative “One Belt, One Way” in 2013-2019. A set of factors was identified and analyzed that contributed to building a constructive dialogue between Beijing and Ankara on cooperation in the New Silk Road projects. The periodization of the political and diplomatic history of coordination of the Chinese and Turkish concepts of creating a single economic space in Eurasia is proposed; the characteristic of its main stages is presented, as well as the legal and institutional framework for the interaction of the two states formed during the negotiations. A review of the joint projects implemented by Turkey and China in the framework of the land and sea Silk Road projects has been completed. It is noted that their quantitative and qualitative parameters confirm the strategic nature of relations between China and Turkey. It is substantiated that the process of matching the integration models proposed by Beijing and Ankara for Eurasia is far from complete due to the presence of certain disagreements regarding the conditions and limits of bilateral cooperation, as well as due to the influence of adverse foreign policy factors.